Morphological and ultrastructural studies on Ulva flexuosa subsp. pilifera (Chlorophyta) from Poland - Messyasz, Beata; Czerwik-Marcinkowska, Joanna; Massalski, Andrzej; Uher, Bohuslav; Rybak, Andrzej; Szendzina, Lidia; Pikosz, Marta (My University, 2013)
Ulva flexuosa subsp. pilifera (Kütz.) M. J. Wynne 2005 (= Enteromorpha pilifera Kützing 1845) was previously found in Argentina, the Czech Republic, Germany, Hungary, Romania, Slovakia and Sweden, recently also in Poland. The genus Ulva was first time described as Enteromorpha. Interestingly, Enteromorpha is used nowadays as a synonym for Ulva, a development which is based on molecular data. The morphologies of both young and mature specimens were studied, and most life cycle stages could be observed. Further, the formation of calcium carbonate crystals on the surface of Ulva thalli seems to influence the arrangement of the cells. A detailed ultrastructural (TEM) analysis of cell walls is presented. The TEM reveals in great details highly complex, irregular structures with stratification lines.
Keywords: green algae; ultrastructure; cell wall; Ulva flexuosa subsp. pilifera; Poland; freshwater Ulva; freshwater Enteromorpha; Ulva; Enteromorpha